Comparative study on the effect of industrial by-products as a replacement of cement in concrete. (2021) - Sharma, Ujjwal; Gupta, Nakul; Saxena, Kuldeep K.
Abstract: In cement industry, the production of cement leads to the formation of CO2 gas that subsequently disposed into the environment. To reduce or eliminate the production of CO2, cement is replaced with the industrial waste product to develop concrete. Therefore, various samples are prepared by replacing the cement with various industrial waste materials such as brick dust, marble dust, and ceramic dust in different proportion of 5%, 7.5%, 10%, 12.5%, 15%, 20%.Tests are conducted to know the mechanical properties of this concrete having MDP (marble dust powder), BDP (brick dust powder) and CDP (ceramic dust powder as replacement to cement. Compressive strength and split tensile strength testing of samples were conducted after curing the specimens for a set duration of 7 days, 28 days and 56 days. Additionally, slump test was done to predict the workability of concrete. In relation to MDP and BDP values of slump for CDP were found to be in decreasing order with increase in the replacement percentage. 10%, 12.5% and 7.5% were the best replacement percentages for MDP, BDP and CDP respectively in case of compressive strength test as well as split-tensile-strength for all days of curing. But CDP could not show the long term effect in strength increment in comparison with the conventional concrete.